Legality of using hypnobirthing in obstetrical and gynecological practice (obgyn doctor) in Indonesia - Rachmad Saleh; Made Warka; Slamet Suhartono; Yovita Arie Mangesti (Technium Social Sciences Journal, 2023)
Healthy life is a constitutional right that every citizen has. Various efforts to achieve a healthy life are carried out in various ways in line with the development of science and technology. This effort is carried out by providing a guarantee of healthy life protection from the time the baby is in the womb. The implementation is to provide health services to pregnant women. Pregnant women generally experience high levels of anxiety.